XIRP2, an Actin-Binding Protein Essential for Inner Ear Hair-Cell Stereocilia - Déborah I. Scheffer; Duan-Sun Zhang; Jun Shen; Artur Indzhykulian; K. Domenica Karavitaki; Yichao Joy Xu; Qinchuan Wang; Jim Jung-Ching Lin; Zheng-Yi Chen; David P. Corey (Cell Reports, 2015)
Hair cells of the inner ear are mechanoreceptors for hearing and balance, and proteins highly enriched in hair cells may have specific roles in the development and maintenance of the mechanotransduction apparatus. We identified XIRP2/mXinβ as an enriched protein likely to be essential for hair cells. We found that different isoforms of this protein are expressed and differentially located: short splice forms (also called XEPLIN) are targeted more to stereocilia, whereas two long isoforms containing a XIN-repeat domain are in both stereocilia and cuticular plates. Mice lacking the Xirp2 gene developed normal stereocilia bundles, but these degenerated with time: stereocilia were lost and long membranous protrusions emanated from the nearby apical surfaces. At an ultrastructural level, the paracrystalline actin filaments became disorganized. XIRP2 is apparently involved in the maintenance of actin structures in stereocilia and cuticular plates of hair cells, and perhaps in other organs where it is expressed.